La France et la Grèce au XXe siècle : des archives à l'histoire - Girard, Maximilien; Béchu, Claire (Mondes méditerranéens et balkaniques (MMB), 2021)
Ever since it gained independence, Greece has maintained a very special relationship with France, more so than with any other country in Europe. Periods of upheaval during the 20th century may have strained the bonds, but the deep connection between the two nations has never come into question. The staying power of this kinship invites us to examine what underpins their close relationship, how it has endured and regenerated, and to examine the ways in which the two countries have continuously interacted over the years. The resources for this study came from the extensive, sometimes little-known archives, in both Athens and Paris, and brought together archivists and historians in a joint effort to go beyond the usual clichés of Philhellenism and Francophilia.